Morphological and isozymic banding pattern study of white grubs (Coleoptera: Melolonthidae) as pest of bark crop in mounth Merapi’s slope. - SUGIYARTO SUGIYARTO (Society for Indonesian Biodiversity, 2008)
White grub (Coleoptera: Melolonthidae) is a group of soil pest at any agrosystem., especially at Salak pondoh (Salacca zalacca (Gaert.)Voss.) crop. The characteristics of this specimen were very crucial to be studied in order to find the exact biocontrol. The aim of this research was to know the characteristics of white grubs (Melolonthidae: Coleoptera) based on morphological and isozyme banding patterns. This research was conducted on August - November 2007 at Sleman and Magelang districts for the morphological purposes, while for the isozyme data were conducted at Sub Laboratory Biology, Central Laboratory of Sebelas Maret University Surakarta. Sample was taken by using stratified random sampling method, on five stations. Polyacrylamide gel electrophoresis (PAGE) using the vertical type was taken to isozyme analysis. The enzyme used in this research were peroxidase and esterase to detect the isozyme banding patterns. The results showed that there was no morphological variation of white grubs (Melolonthidae: Coleoptera) at salak pondoh agroecosystem in Mounth Merapi’s slope. Based on this character, there was one species of white grub found, i.e. Holotrichia javana. There was a genetic variation based on the variation of isozyme banding patterns.© 2008 Jurusan Biologi FMIPA UNS Surakarta.Key words: white grubs, isozyme, Merapi mount, bark.